Could Childcare Services Improve Women’s Labor Market Outcomes in Indonesia? - Halim, Daniel; Johnson, Hillary; Perova, Elizaveta (World Bank, Washington, DC, 2019)
In this brief, the authors explore whether lack of access to childcare is a constraint to female labor force participation (LFP) in Indonesia, a country where female LFP lags far below the regional average. Using household and labor force survey data, we find that low female LFP is linked to unsatisfied childcare needs - after childbirth, lack of access to informal childcare is associated with a longer absence from the workforce for women and a switch into less lucrative occupations or unpaid family work.